Two Pot and One Pot Synthetic Methodologies of Hantzsch Pyridines - Farooq, Saba; Ali Munawar, Munawar; Zainab, Ngaini (Bentham Science Publishers, 2018)
Hantzsch pyridines are conspicuous nitrogen-holding heterocyclic compounds and different procedures have been worked out for their synthesis. Hantzsch pyridines have a variety of methods for their synthesis but according to the literature survey, two pot synthetic route is more developed than one pot due to a vast variety of catalysts becoming cheap, economical, eco-friendly and recyclable. However, researchers synthesized Hantzsch pyridines under different methodologies due to the molecule’s reactivity and requirement of the chemist. An up-to-date first review related to the two pot and one pot synthetic methodologies of Hantzsch pyridines gives the most valuable basic skeleton to derive the biologically active compounds, which are frequently used in the pharmacological field. The main objective of this review is to explore all the synthetic modifications in its methodologies, which are fruitful, especially for the synthetic chemists and therapeutical industry.